The association between perchlorate in drinking water and height and weight of children and adolescents in Southwest China: a retrospective cross-sectional study - Hongyu Guo; Shimiao Zong; Li Yong; Yang Jiang; Ling Qin; Liang Zhou; Qiaoqiao Ren; Xufang Gao; Fayang Kang; Wei Huang; Jianyu Chen; Li Zhang (Frontiers Media S.A., 2023)
ObjectiveTo investigate the association between the concentration of perchlorate in drinking water and the height and weight of children and adolescents in Sichuan Province.MethodsPerchlorate in the drinking water of 24 counties in Sichuan Province from 2021 to 2022 was detected and analyzed, 66 drinking water samples were collected, and the content of perchlorate in drinking water during the wet season and dry season was detected by ultra-high performance liquid chromatography in series. The linear mixed effect model was used to estimate the relationship between perchlorate in drinking water and the height and weight of 144,644 children and adolescents, and 33 pieces of local average wage data were used as confounding factors for quality control.ResultsAfter controlling the age, gender, and local economic situation, we found that the concentration of perchlorate in drinking water increased by 10 μg/L is associated with a 1.0 cm decrease in height and a 1.6 kg decrease in weight in children and adolescents (p < 0.05).ConclusionThe concentration of perchlorate in drinking water may be negatively correlated with the height and weight of children.